Contingency Leadership of the Principal and Student Academic Performance - Villasis Padilla, María Julia (2020)
This article is the summary of an investigation that aims to establish whether there is a relationship between the contingency leadership of the principal and the academic performance of the students of the I cycle of the Professional School of Primary Education in the Faculty of Education of the National Hermilio University Valdizán in the city of Huánuco in 2017. The type of research is descriptive correlational, cross-sectional. The study is framed by teachers, administrative staff and students of the I cycle of the Professional School of Primary Education in the Faculty of Education of the National University Hermilio Valdizán in the city of Huánuco. As an instrument, the questionnaire questionnaire and the data collection sheet (academic records) were used. The validity of the instruments was made through expert judgment. Among the most important conclusions it can be pointed out that there is a direct and significant relationship between the contingency leadership of the principal and the academic performance of the students of the I cycle of the Professional School of Primary Education in the Faculty of Education of the National University Hermilio Valdizán in the city of Huánuco in 2017.